The challenges of construction project managers in managing construction during the transition toward endemic / Eiman Danieal and Kartina Alauddin - Danieal, Eiman; Alauddin, Kartina (2023)
Endemic can be defined as the constant presence and/or prevalence of the disease or infectious agent in a population within a geographic or the disease that is consistently present but manageable by the communities. The construction workforce was worried about being redundant or relying on furlough schemes to express concern about the construction industry’s future. The aim of this paper is to explore the adaptation of construction managers through challenges faced as shifting towards endemic. The research objective is to identify the challenges of construction managers in managing construction during the transition towards the endemic. The quantitative method was chosen for this research methodology, and the questionnaire was distributed to 254 Construction Project Managers in Pahang, Malaysia. The data from the questionnaires will be analyzed using SPSS version 28.0, and descriptive analysis will be used to present the data. Finances crisis is a critical challenge for Construction Project Managers to face in managing construction during the transition towards the Endemic.